PELABELAN GRACEFUL SISI-GANJIL PADA GRAF WEB W(2,n) - Rizky, Putri Dentya; Ratnasari, Lucia; ., Djuwandi (MATEMATIKA, 2014)
Let G = (V(G),E(ðº)) be a graph with vertex set ð‘‰(ðº) and edge set ð¸(ðº). Assume that graph G have ð‘ž edge. Graceful edge-odd labeling is a bijective map Â ð‘“ âˆ¶ ð¸(ðº) â†’Â  {1, 3, 5,â€¦,2ð‘ž â€“ 1} that resulting map ð‘“+ : ð‘‰(ðº) â†’ {0,1,2,â€¦,2ð‘ž âˆ’1} with Â such as obtained different edge label. Graph G ia called Graceful edge-odd labeling if there is graceful edge-odd labeling on G. Let Â and Â are two cycle graph with vertex set Â and . Graph Â is obtained by conected every vertex from Â to Â  such as we have edge Â Graph Web W(2,n) is a graph obtained by adding a pendant edge on each outer cycle vertex from graph . In this paper we will discussed about Graceful edge-odd labeling on Web (2,ð‘›) graph and we have that Web W(2,ð‘›) graph is graceful edge odd graph for n odd.